Local government accountability – financial, efficiency, effectiveness and sustainability performance reports : stakeholder perspectives - Quinlivan, Michael Dale (Curtin University, 2012)
The question posed in this study was whether local government is held accountable for their financial management, efficiency, effectiveness and sustainability and if local government reports contribute to this. In this study perceptions of how residents form their views about the performance of their local government were gained by interviewing residents and senior managers. Three local governments differing in the size of the organisation, the demography of the residents, and their urban environment took part in the study. A qualitative methodology within the constructivist paradigm was used with the rigour of the study being judged in terms of its method and analysis, and the findings and recommendations assessed against quality criteria particularly its usefulness in the real world of local government.Using a grounded research approach, the study found that residents’ perceptions of local government are highly subjective and influenced by many factors including trust in the local government, personal experience, public perceptions and personal values. Using economics of information theory in which the cost of information is balanced against the benefits of the information, residents’ behaviour was classified into four categories: detached, vicarious, specific purpose and engaged. A tentative model of assurance emerged from the findings. The model provides a means of explaining the personal, institutional and exogenous conditions that affect the benefits and cost to residents of performance information. The emergent model was used to understand issues about the accountability of local government, and implications for community engagement, models of management and local government sustainability programmes.